Students’ Characters During the Covid-19 Pandemic at SMAN 46 Jakarta - Rohmah, Siti; Azis, Abdul; Wahid, Abdul; Novebriansyah, Rizky; Mamonto, Merdi F. (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to analyze students’ characters during the Covid-19 pandemic. In this study, the researchers employed the quantitative method with a survey design and quantitative data analysis. Samples were selected through the accidental sampling technique, resulting in 200 respondents from 972 students of SMAN 46 Jakarta. The instrument for data collection was the student character instrument constructed by Indonesia’s Ministry of Education and Culture (2017) consisting of 43 statements. Concerning reliability, this instrument obtained a Cronbach’s alpha value of 0.744. The results of the measurement of students’ characters indicated that the respondents had very good character (a mean value of 3.39 with a standard deviation of 14.32 on a scale of 4). Furthermore, the highest indicators were found in nationalism, togetherness, and responsibility towards oneself. It showed that online learning at home can make students’ families internalize character values that cannot be separated from the role of parents and teachers in carrying out positive activities while interacting and coordinating in guiding students patiently. These findings need to be considered to achieve success in shaping the character of students in the present and the future.